Uma experiência coma taxonomia digital de bloom aplicada ao ensino da matemática. - SILVA, Taynara Oliveira Ferreira da (Universidade Federal do Tocantins, 2023)
There are several instructional mechanisms that assist the teacher in the planning of his classes, but in order to choose such instruments, the teacher requires careful observation in order to be able to rely on the method appropriate to the student's cognitive ability, increasing levels of learning. This paper analyzes the application of Bloom's Digital Taxonomy in Mathematics teaching, whose main objective is to present this systematics as a guiding strategy of the practice-teacher aiming at experiential technological learning. The problem that gave rise to such research is expressed as follows: How can Bloom's Digital Taxonomy influence the Mathematics teaching plan in order to structure the student's learning process? In order to complement the guiding question, documentary research was used as a methodology for the development of this study, as well as the presentation of some didactic proposals that were developed in the classes of Mathematics Fundamentals and guided by the Taxonomy of Educational Objectives updated for the Digital Age. As a result, the importance of the definition of educational objectives in line with the levels of human cognition, the ease of defining teaching goals using the aforementioned instrument, and the functionality of this systematics when introduced in class are pointed out.